2008
DOI: 10.1158/0008-5472.can-07-6171
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Receptors, Novel Targets of Sulforaphane Identified by Proteomic Analysis in Caco-2 Cells

Abstract: Cancer chemopreventive activity of sulforaphane has been predominantly associated with its ability to induce phase II detoxification enzymes. In the present study, novel targets of sulforaphane were identified and characterized using a proteomics approach. Two-dimensional gel electrophoresis and mass spectrometry were used to produce protein profiles of human colon adenocarcinoma Caco-2 cells treated with 5 Mmol/L sulforaphane for 48 h and control cells (0.05% DMSO). Gel comparisons showed the down-regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Thus, SFN could sensitize cancer cells to apoptosis through DR5 upregulation which presents another potential mechanism of chemoprevention (83,84). Using proteomics approach, recently some novel targets of SFN were identified and characterized (85). Human colon adenocarcinoma cell (Caco-2) was treated with 5 μM SFN for 48 h and serotonin receptor 5-HT was downregulated to undetectable levels as compared to the controls (85).…”
Section: Receptors As Molecular Targets For Peitc and Sfnmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, SFN could sensitize cancer cells to apoptosis through DR5 upregulation which presents another potential mechanism of chemoprevention (83,84). Using proteomics approach, recently some novel targets of SFN were identified and characterized (85). Human colon adenocarcinoma cell (Caco-2) was treated with 5 μM SFN for 48 h and serotonin receptor 5-HT was downregulated to undetectable levels as compared to the controls (85).…”
Section: Receptors As Molecular Targets For Peitc and Sfnmentioning
confidence: 99%
“…Using proteomics approach, recently some novel targets of SFN were identified and characterized (85). Human colon adenocarcinoma cell (Caco-2) was treated with 5 μM SFN for 48 h and serotonin receptor 5-HT was downregulated to undetectable levels as compared to the controls (85). It was suggested that the activation of neurotransmitter receptors followed by initiation of cyclic AMP signaling might be crucial events in colon carcinoma progression.…”
Section: Receptors As Molecular Targets For Peitc and Sfnmentioning
confidence: 99%
“…Other potential targets include kinases, transcriptional factors, transporters and receptors [21][22][23][24]. Since both Nrf2 and TrxR-1 can play dual roles in cancer [25][26][27][28] glutamine, penicillin (100 U/ml) and streptomycin (100µg/ml) under 5% CO 2 in air at 37 o C.…”
Section: Introductionmentioning
confidence: 99%
“…b Apoptotic HT29 cell after incubation with 5-HT 1A antagonist (5 M) for 48 h. c Apoptotic HT29 cell after incubation with 5-HT 1B antagonist (5 M) for 48 h. d Comparison of apoptotic index between three test groups and negative control; *P < 0.05; **P < 0.01 increases in patients with cancer, comprising 25% of this sub-population (Huerta et al 2006;Pezzella et al 2001). It seems plausible that introducing phytochemicals which have the most interactions with speciWc monoamine receptors (expressed highly in colorectal cancer tissues) may initiate new approaches in control of this malignancy (Mastrangelo et al 2008). There is ongoing debate about whether antidepressant medications may increase or decrease the risk of colon cancer.…”
Section: Discussionmentioning
confidence: 99%